A microfluidic chip‐based fluorescent biosensor for the sensitive and specific detection of label‐free single‐base mismatch via magnetic beads‐based "sandwich" hybridization strategy. Issue 15 (2nd August 2013) - Wang, ZongWen; Fan, YingWei; Chen, JinFa; Guo, Ying; Wu, WeiHua; He, Ye; Xu, LiangJun; Fu, FengFu
<x xml:space="preserve">Abstract</x> A novel microfluidic chip‐based fluorescent DNA biosensor, which utilized the electrophoretic driving mode and magnetic beads‐based "sandwich" hybridization strategy, was developed for the sensitive and ultra‐specific detection of single‐base mismatch DNA in this study. In comparison with previous biosensors, the proposed DNA biosensor has much more robust resistibility to the complex matrix of real saliva and serum samples, shorter analysis time, and much higher discrimination ability for the detection of single‐base mismatch. These features, as well as its easiness of fabrication, operation convenience, stability, better reusability, and low cost, make it a promising alternative to the SNPs genotyping/detection in clinical diagnosis. By using the biosensor, we have successfully determined oral cancer‐related DNA in saliva and serum samples without sample labeling and any preseparation or dilution with a detection limit of 5.6 × 10−11 M, a RSD (n = 5) < 5% and a discrimination factor of 3.58–4.54 for one‐base mismatch.